Orthodontic considerations in bone graft selection for alveolar cleft repair - Rohaya Megat Abdul Wahab; Ng, Wan Ching; Farinawati Yazid; Nur Atmaliya Luchman; Shahrul Hisham Zainal Ariffin (Penerbit Universiti Kebangsaan Malaysia, 2020)
The enthusiastic development of non-autogenous bone graft materials to correct oral cleft defects in dentistry is founded on arguments of post-operative morbidity and quantity limitation when using conventional iliac crest bone grafts. While success in tooth movement is usually reported for the grafted extraction socket, the results cannot be extrapolated to congenital alveolar clefts as there are differences in terms of vasculature and soft tissue support. This paper provides an overview of the dental and skeletal anomalies in cleft patients, followed by the orthodontic implications of cleft correction and, lastly, a review of the available evidence in bone grafts used for alveolar clefts alone. The non-autogenous grafts used are derived from another human (allografts), animal (xenografts), synthetic bones (alloplasts) or the latest tissue-engineered graft material. The main advantage of using these grafts is a reduction in the number of operative sites. The drawbacks are cost, reduced tooth movement, possibility of root resorption and host reaction. Tissue-engineered grafts seem promising but there is still a lack of clinical trials in human subjects. Important properties related to orthodontics are the graft resorption rate, along with the effect on root resorption and tooth movement rate. To date, autogenous bone grafts remain the first choice for cleft repair.